2015
DOI: 10.1097/ana.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Sedation for Electroencephalography With Dexmedetomidine or Chloral Hydrate

Abstract: The differences of DEX and CH in EEG power did not change the EEG qualitative interpretation, which was similar with the 2 drugs. Other studies comparing natural sleep and sleep induced by these drugs are needed to clarify the clinical relevance of the observed EEG quantitative differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…For example, it would have been convenient to compare the study groups with patients who received neither REMI nor DEX, but there were too few patients corresponding to that protocol. Another useful physiological parameter that may be impacted by choice of anesthetic agents is the power in frequency bands of the local field potential (such as effects seen in selective bands of the electroencephalogram [55], although a previous study suggested that beta power is unaffected in the MER [21]). Lastly, an important question of interest is whether patients who received DEX+REMI had similar postoperative outcomes as the group who only received REMI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it would have been convenient to compare the study groups with patients who received neither REMI nor DEX, but there were too few patients corresponding to that protocol. Another useful physiological parameter that may be impacted by choice of anesthetic agents is the power in frequency bands of the local field potential (such as effects seen in selective bands of the electroencephalogram [55], although a previous study suggested that beta power is unaffected in the MER [21]). Lastly, an important question of interest is whether patients who received DEX+REMI had similar postoperative outcomes as the group who only received REMI.…”
Section: Discussionmentioning
confidence: 99%
“…The signals were recorded by an EEG device (Nihon Kohden, Japan) using electrode positioning that adhered to 10-20 international standards (12). The EEG was monitored after using 50 mg/kg of chloral hydrate to fall children to sleep (13).…”
Section: Sleep Eeg and Qeegmentioning
confidence: 99%
“…Many sedative drugs that act on the central nervous system interfere with brain waves, such as ketamine, propofol, and sevoflurane [ 2 , 3 ]. Previous studies had shown that both chloral hydrate (CH) and dexmedetomidine (DEX) were utilized for sedation during EEG, and didn't interfere with brainwaves [ 4 ].…”
Section: Introductionmentioning
confidence: 99%